Techno-Economic Assessment Guidelines for CO2 Utilization - Zimmermann, Arno W.; Wunderlich, Johannes; Müller, Leonard; Buchner, Georg A.; Marxen, Annika; Michailos, Stavros; Armstrong, Katy; Naims, Henriette; McCord, Stephen; Styring, Peter; Sick, Volker; Schomäcker, Reinhard (Frontiers in Energy Research, 2020)
Carbon Capture and Utilization (CCU) is an emerging technology field that can replace fossil carbon value chains, and that has a significant potential to achieve emissions mitigation or even “negative emissions”—however in many cases with challenging technology feasibility and economic viability. Further challenges arise in the decision making for CCU technology research, development, and deployment, in particular when allocating funding or time resources. No generally accepted techno-economic assessment (TEA) standard has evolved, and assessment studies often result in “apples vs. oranges” comparisons, a lack of transparency and a lack of comparability to other studies. A detailed guideline for systematic techno-economic (TEA) and life cycle assessment (LCA) for CCU technologies was developed; this paper shows a summarized version of the TEA guideline, which includes distinct and prioritized (shall and should) rules and which allows conducting TEA in parallel to LCA. The TEA guideline was developed in a co-operative and creative approach with roughly 50 international experts and is based on a systematic literature review as well as on existing best practices from TEA and LCA from the areas of industry, academia, and policy. To the best of our knowledge, this guideline is the first TEA framework with a focus on CCU technologies and the first that is designed to be conducted in parallel to LCA due to aligned vocabulary and assessment steps, systematically including technology maturity. Therefore, this work extends current literature, improving the design, implementation, and reporting approaches of TEA studies for CCU technologies. Overall, the application of this TEA guideline aims at improved comparability of TEA studies, leading to improved decision making and more efficient allocation of funds and time resources for the research, development, and deployment of CCU technologies.